2022
DOI: 10.3390/bs12060173
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits of Croatian University Students with Internet Addiction

Abstract: Specific personality traits may predispose individuals to various forms of addictive behaviors. This study aimed to investigate the association between personality traits of university students and Internet addiction (IA). A sample of 1051 university students was recruited from the largest university in Eastern Croatia. A structured anonymous questionnaire that included questions regarding students’ sociodemographic information and Internet usage patterns, the Young Internet Addiction Test and Big Five Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Regarding sociodemographic correlates, the existing literature is inconclusive on the association between age and IA. Some studies showed no association (e.g., Canan et al, 2012;Younes et al, 2016) while some studies showed a significant negative association between age and IA among university students (e.g., Kumcagiz, 2019;Miskulin et al, 2022;Orsal et al, 2013;Romero-López et al, 2021). In another study, also showed that age was negatively related to depression.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding sociodemographic correlates, the existing literature is inconclusive on the association between age and IA. Some studies showed no association (e.g., Canan et al, 2012;Younes et al, 2016) while some studies showed a significant negative association between age and IA among university students (e.g., Kumcagiz, 2019;Miskulin et al, 2022;Orsal et al, 2013;Romero-López et al, 2021). In another study, also showed that age was negatively related to depression.…”
Section: Discussionmentioning
confidence: 95%
“…Regionally, Internet addiction has a greater impact on Internet users in developed areas, such as in Europe and the United States [ 48 , 49 ]. Studies also found that those with greater neuroticism are more likely to become addicted to the Internet [ 50 , 51 ]. Heterogeneity also exists in terms of gender, age, and social class.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main theme of Addictive Behavior (0.75, 0.58) was determined to be associated with the subthemes of Personality Inventory, Cultural Factor, Anxiety Disorder, Sex Factors, Personality, Reproducibility, Interpersonal Relations, and Child Psychology themes. These studies on Personality Inventory [ 107 ], Cultural Factor [ 102 ], Anxiety Disorder [ 108 ], Sex Factors [ 102 ], Personality [ 95 ], Reproducibility [ 109 ], Interpersonal Relations [ 110 ], and Child Psychology [ 98 ] support the findings with regards to the Addictive Behavior cluster network.…”
Section: Resultsmentioning
confidence: 74%